Variación de temperatura en nacedora y su efecto sobre ventana de nacimiento y calidad del pollito Cobb 500 - Vera Vera, Abel Alberto (2025)
The present study evaluated the effect of temperature variation in the hatcher on hatch window and chick quality in Cobb 500 broilers. A completely randomized experimental design was used with four temperature treatments (37.5 °C, 37.3 °C, 37.1 °C, 36.9 °C) during the final stage of incubation. Variables measured included the number of chicks hatched in different hatch windows, yolk sac absorption, weight gain, feed intake, feed conversion, and carcass yield. The results showed significant differences (p < 0.05) in chicks hatched at 492 and 504 hours. At 37.5 °C, fewer chicks hatched at 492 hours compared to the higher number observed at 504 hours. Significant differences (p < 0.05) were also found in yolk sac absorption at day 3 and in feed intake, although no differences were observed in final weight or carcass yield. It is concluded that temperature variation in the hatcher influences hatch uniformity and yolk sac absorption during the first days of life, although it does not affect the final performance of the broiler.